Improving Efficiency of Asset Management in the Context of Ensuring Competitiveness of Mechanical Engineering Enterprises in Developing Countries - Yepifanova, Irina M. (Journal of Reviews on Global Economics, 2019)
The research paper deals with the formation of new scientific solutions regarding increasing the efficiency of asset management in the context of ensuring the competitiveness of mechanical engineering enterprises in developing countries. The study noted the disparity in the development of economically developed and developing countries. It is revealed that one of the main aspects of such disparity is the competitiveness of both the economies of the countries as a whole, and of individual industries and enterprises. At the same time, the importance of ensuring the competitiveness of mechanical engineering enterprises in developing countries was noted, taking into account their potential and opportunities for stimulating GDP and employment growth in these countries. The relationship between the competitiveness of mechanical engineering enterprises and their asset management is established. The main problems of asset management at the mechanical engineering enterprises in the developing countries are localized, and the ways of their elimination are proposed taking into account the division of enterprises into those operating as part of the transnational and foreign corporations, large enterprises with national capital, medium and small enterprises with national capital. A considerable range of problems regarding the asset management in small and medium enterprises was noted. Directions of further scientific researchers are suggested.